Open-Competitive Bidding in Japan’s Public Works Sector and Foreign Contractor Access: Recent Reforms are Unlikely to Meet Expectations - Gray, Jon R. (Columbia Journal of Asian Law, 1996)
In January 1994, responding to U.S. pressure and a spate of construction-related scandals, the Government of Japan adopted an “Action Plan on Reform of the Bidding and Contracting Procedures for Public Works” (hereinafter “Action Plan”). The Action Plan, which was subsequently incorporated into the 1994 U.S.-Japan Public Works Agreement, contained comprehensive measures to improve foreign contractor access to Japan’s public sector construction market by making public bidding procedures fair, open and transparent. While complaints about access to Japan’s construction market often take a back seat to disputes surrounding the automobile and semiconductor industries, the sheer size of Japan’s public works sector has stirred the interest of U.S. construction firms and has prompted repeated attempts to establish a foothold in the Japanese market. These attempts in the past, however, have been thwarted by opaque licensing and bidding procedures that effectively precluded foreign contractors and design firms from meaningful access to the market. Prior to the Action Plan, Japan’s “designated competitive bidding procedures” for public works projects had the effect of permitting only government designated contractors to bid on public works projects and excluded most foreign participants. The United States attempted to address these procedural impediments to market access through bilateral agreements, the most significant being the Major Projects Arrangements in 1988. As discussed herein, these pre-1994 bilateral public works agreements were limited in scope and it is questionable whether meaningful systemic changes were effected. The 1994 Action Plan was structured to address the deficiencies in these prior agreements and to expand the range of projects subject to the reforms.